Decision leadership : empowering others to make better choices - Moore, Don A., 1970-; Bazerman, Max H. (Ascent Audio, 2022)
A fresh, research-driven playbook for how successful leaders can maximize the potential of others When we think of leaders, we often imagine lone, inspirational figures lauded for their behaviors, attributes, and personal decisions, and leadership books often reinforce that view. However, this approach ignores a leader's mission to empower others. Applying decades of behavioral science research, Don A. Moore and Max H. Bazerman offer a passionate corrective to this view, casting today's organizations as decision factories in which effective leaders are decision architects, enabling those around them to make wise, ethical choices consistent with their own interests and the organization's highest values. As a result, a leader's impact grows because it ripples out instead of relying on one individual to play the part of heroic figure. Filled with real-life stories and examples of the structures, incentives, and systems that successful leaders have used, this playbook equips each of us to facilitate wise decisions.